Modeling the microscale contact status in chemical mechanical polishing process. (15th September 2022) - Wang, Lin; Zhou, Ping; Yan, Ying; Guo, Dongming
Highlights: A new concept of "effective contact spots" to equivalent random contact spots. An MRR model considering the micro-scale chemical-mechanical synergy. Theoretically explain the influence of contact state on MRR of various materials. Proposed the parameters reflecting the influence of contact state on MRR. A method to determine the feasible region of contact state ensuring stable MRR. Abstract: The micro-scale contact status between pad and workpiece surface plays one of the most significant roles in determining the material removal rate (MRR) during the chemical mechanical polishing (CMP) process. To evaluate the contribution of random contact status to the material removal process, the paper proposed a novel concept of "effective contact spots". It represents the probability of randomly distributed pad asperities sliding across a given coordinate point on the workpiece surface. Furthermore, mechanical removal capacity parameter γ and chemical reaction capacity parameter β were defined to mathematically model the material removal process from a micro-scale chemical-mechanical synergistic perspective. To validate the model, a series of CMP tests (with in-situ conditioning) were conducted on three types of materials (BK7 glass, fused silica, and Si). The real contact status was also measured and analyzed statistically after being conditioned with two types of conditioners. Experimental observations and theoretical analysis results indicated that the chemical-mechanical synergism was the fundamental mechanism for the contribution of the micro-scale contact status to the material removal process. Resulting in the fact that the real contact ratio, radius, and spacing of the real contact spots play different dominant roles on MRR for different materials. Moreover, solution strategies in this study can provide the knowledge needed for improving the material removal stability, and further enable predictive control on the polishing or conditioning recipe before a non-ideal contact status result in an unexpected material removal rate. Graphical abstract: Image, graphical abstract